«Dio protegga l’Italia, guai a chi la tocca!». Il Risorgimento nazionale attraverso le lettere di alcune patriote - Angela Russo (Storia delle Donne, 2011)
In the last thirty years, women’s history and gender studies have analyzed the 19th century and the Risorgimento, emphasizing women’s role in the public arena thus making the Risorgimento period more complex and articulated to our eyes. Women have covered several different roles: in fact there were militant women organizing and serving on committees, financing military projects, fighting in the battlefields; there were also women who offered their support to exiled or imprisoned patriots and women who have preferred to write in order to motivate men and prepare for action. Maybe because of a sense of shame and reserve, these women have often kept their adventurous and rebellious life in a closet. For this reason their letters, which we are presenting a selected choice of, are particularly precious: they allow us to better understand political ideas and convictions and to uncover some of the contributions they made toward the process of nation building and ultimately unification.